(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Recently women have to carry all the responsibilities from domestic point of view and external matters. Women are Dharan of Adharaniya Vega due to their busy work schedule. The total evidence of night duties, lack of proper nutrient, fast food, junk food, physical and mental stress from house and office gives invite the diseases. Major symptom in Kaphaja Yonivyapada is Yonigat shwetastrav and Yonikandu. Karanj Taila acts as good Kaphashamak and Sampraptibhanga. Udumbaradi taila reveals that they possess Shodhana, Ropana, Vedanasthapak properties. Patients reduced the symptoms using Karanj taila and Udumbaradi taila in Kaphaja Yonivyapada. This paper presents, study the effect of Karanj taila and Udumbaradi taila Yoni pichu Dharan in Kaphaja Yonivyapada and successfully used Karanj taila and Udumbaradi taila Yonipichu Dharan symptoms in Kaphaja Yonivyapada. The effect of these Taila on 60 patients given this treatment for 21 days, Karanj taila has provided relatively better relief in Yonikandu than Udumbaradi taila. Udumbaradi taila has given relatively better relief than Karanj taila in Yonigat shwetastrava symptom of Kaphaja Yonivyapada. The result shows that, Karanj taila and Udumbaradi taila gave better relief in Yonikandu and Yonigat Shwetastrava respectively in Kaphaja Yonivyapada. To provide better results for women suffering from Kaphaja Yonivyapada and to make their life more comfortable with the help of Ayurvedic formulations with minimal side effect.